GAMBARAN KECERDASAN EMOSIONAL PADA SISWA SMKN 1 JAKARTA - Dwi Wulandari (Journal of Research and Measurement in Psychology, 2017)
Abstract The aim of this article is to know the description of emotional intelligence to vocational high school's student in Jakarta. This research took at SMKN 1 Jakarta from February 2012 until June 2012. Populations of the research are 800 students which are the student's entire of SMKN 1 Jakarta. Sample in this research are 50 students from first and second grades. Researcher uses a description method by quantitative approach. Technique to take the sample is by using incidental sampling technique. To collect the emotional intelligence's data, researcher uses an emotional intelligence's scale by likert and then, analyze it with statistic description. The result shows that SMKN 1 Jakarta's students have a high emotional intelligence. The data shows-that 50 respondences (100%) have a high level category of emotional intelligence. Keywords : Emotional Intelligince, Vocational High School's Students